The Effectiveness of Soybean Meal, Zn, and Cr Supplementation in the Ration on Total Erythrocyte, Hemoglobin Levels, and Packed Cell Volume in Rambon Goats - Muhtarudin, Muhtarudin; Lidyana, Ayu; Farda, Fitria Tsani; Hartono, Madi; Sirat, Muhammad Mirandy Pratama (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
This study aims to evaluate the effects and identify the optimal treatment of adding soybean meal, zinc (Zn), and chromium (Cr) on the total erythrocyte count, hemoglobin levels, and packed cell volume in Rambon goats. The research was conducted from November 2022 to January 2023 at the goat pen of the Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. Total erythrocyte count and packed cell volume were assessed at the Pathology Laboratory of the Lampung Veterinary Center, while hemoglobin levels were analyzed at the Laboratory of Physiology and Animal Reproduction, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung.The experiment involved 12 male Rambon goats and employed a Randomized Block Design (RBD) based on body weight, with four treatments and three replicates. The treatments were as follows: P1: Basal ration, P2: Basal ration 90% + 10% soybean meal, P3: Basal ration + organic minerals (40 ppm Zn lysinate + 0.3 ppm Cr lysinate), and P4: Basal ration 90% + 10% soybean meal + organic minerals (40 ppm Zn lysinate + 0.3 ppm Cr lysinate). Data were analyzed using analysis of variance (ANOVA) at a significance level of 5%.The observed variables included total erythrocyte count, hemoglobin levels, and packed cell volume. The results indicated that the addition of soybean meal, Zn, and Cr had no significant effect (P>0.05) on total erythrocyte count, hemoglobin levels, or packed cell volume. However, the supplementation was found to maintain normal values for these parameters, with a tendency to increase total erythrocyte count (P4), hemoglobin levels (P3), and packed cell volume (P2) within normal limits.